Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1017/aee.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Children and Young People's Experience of the Natural World: Teachers' Perceptions and Observations

Abstract: This study explores the observations and perceptions of environmental education centre officers and teachers regarding children's experiences with nature. The study also explores the officers' and teachers' perceptions of the potential of using nature experiences in environmental education. A thematic analysis of data from interviews with 13 officers and 8 high school teachers in Sydney, Australia, revealed a widely held perception that children and young people have limited experience with natural settings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Coinciding with the findings of previous studies (Fägerstam, 2012;Gilberston, 2012), happiness is the emotion most frequently attributed to the images of natural environments (landscapes). The higher frequency of attributions of happiness may be the result of feelings of agreeableness generated by the recall of pervious experiences in similar settings, which reinforces, as posited in the theory of connectedness to nature, the importance of contact with nature for the development of positive emotional traits (Mayer and Frantz, 2004;Schultz and Tabanico, 2007;Mayer et al, 2009;Olivos and Clayton, 2017;Mena et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Coinciding with the findings of previous studies (Fägerstam, 2012;Gilberston, 2012), happiness is the emotion most frequently attributed to the images of natural environments (landscapes). The higher frequency of attributions of happiness may be the result of feelings of agreeableness generated by the recall of pervious experiences in similar settings, which reinforces, as posited in the theory of connectedness to nature, the importance of contact with nature for the development of positive emotional traits (Mayer and Frantz, 2004;Schultz and Tabanico, 2007;Mayer et al, 2009;Olivos and Clayton, 2017;Mena et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…This supposition has supported a range of popular and academic claims about the importance of children's connections with nature – whether in terms of physical, embodied learning, play or presence in forests or other natural spaces, or children's understanding of natural processes (especially the production, management and divestment of resources like water, energy and food). Thus, a range of studies and systematic reviews have demonstrated the positive outcomes for children and young people of better connectedness with nature in terms of: improved self‐esteem, behaviour, creativity and empathy (Faber Taylor & Kuo, ); diverse developmental characteristics and performance in standardised educational tests (Armour & Sandford, ; Austin et al., ); the adoption of pre‐environmental knowledges and behaviours (sometimes termed “biophilia”; Fägerstam, ; Payne, ); participation and social inclusion in “local” communities (Wake & Birdsall, ); varied health outcomes, ranging from reduced prevalence of obesity (Durand et al., ) to improved cell ageing profiles (Olafsdottir et al., ) and from improved mental health (Biddle & Asare, ) to lower allergy rates (Chawla, ).…”
Section: (Re)thinking (Re)connection: Childhoods–natures and Nexus Thmentioning
confidence: 99%
“…Despite two decades of environmental education, it is reported that many children fear actually being in nature (Fagerstam 2012). Most students experience nature vicariously through reading, television, and the classroom (Kellert 1996).…”
mentioning
confidence: 99%